Reconstructing village spatial layout to achieve rural revitalization: a case from a typical township in China - Zhu, Zhiyuan; Wang, Huaizhou; Yang, Jihao; Feng, Yongzhong (Frontiers in Sustainable Food Systems, 2023)
Rural revitalization is a strategy proposed by China to address the imbalance and insufficiency of urban and rural development. The purpose of village system reconstruction is to optimize the rural spatial structure and realize the efficient allocation of resource elements, which is of great significance to the overall revitalization of rural areas. This research adopts the analytic hierarchy process (AHP), the multi-index comprehensive evaluation method, and the GIS spatial analysis, taking Zhiyang Town as a case, reconstructing the index selection of the village-level system, putting forward a set of complete classification systems through the selecting village scale, resource conditions, social economic development level, industry, and other related data index, and building a village-level evaluation system. The 25 villages in Zhiyang Town were divided into four classes. Different development paths are proposed for different levels of villages. The evaluation of the village development level and reconstruction path of the village hierarchy system has certain practical guiding values for rural construction, which are of great significance for realizing rural revitalization.